7E analysis of a conceptual utility-scale land-based solar photovoltaic power plant - S., Sreenath; K., Sudhakar; A. F., Yusop (Elsevier, 2021)
Large scale solar PV systems have a high priority among clean energy initiatives across the world. A comprehensive and more realistic analysis of the solar PV power plant is not reported yet. This study performs the energy, exergy, economic, environmental, energoeconomic, exergoeconomic, and enviroeconomic (7E) analysis of conceptual 5Â MW land-based solar photovoltaic power plant in five locations of Malaysia. Solar irradiation and climate data for each location are collected from the meteorological database of RETScreen software. The energy, economic, and environmental performance of the proposed solar PV system is predicted using RETScreen software. The exergy, energoeconomic, exergoeconomic, and enviroeconomic parameters are assessed using Microsoft excel based mathematical model. It is observed that the solar PV system proposed for all the selected locations will operate sufficiently well with a minimum 80 performance ratio (PR). The capacity utilization factor (CUF) varied between 17.04 (Site 2) and 14.25 (Site 4). The exergy efficiency varied between 11.35 (Site 2) and 12.65 (Site 4). The lowest value of the Payback period and LCOE is estimated to be 7.9 years and 0.102 respectively for the Site 2 solar PV system with consideration of GHG reduction revenue. The reduction in the GHG emissions is highest in Site 2, which is equivalent to 975.4 acres of forest and 1479.8 tonnes of waste recycled. Site 2 has the lowest exergoeconomic and energoeconomic parameters, as well as the highest enviroeconomic parameter. Hence, it is concluded that Site 2 has the best condition for implementation of solar PV system (80 PR, 17.04 CUF, 11.35 exergy efficiency, 7.9 years simple payback period, 17.10 internal rate of return, 0.102 USD LCOE, 4291 tCO2 avoided/annum, 0.0147Â kWh/USD, 1.096 kW/USD, 42,916 USD) based on 7E analysis.